My friend Flicka - O'Hara, Mary. (Philadelphia : Lippincott, 1973)
Eleven year old Ken's devotion to his colt causes him to assume the responsibilities of growing up.
Booklist.
Horn Book.
Library Journal.
6.8
6.8
5-8.
Keywords: Fathers and sons -- Wyoming -- Fiction; Horses -- Wyoming -- Fiction; Human-animal relationships -- Wyoming -- Fiction; Ranch life -- Wyoming -- Fiction; Horses -- Fiction; Wyoming -- Fiction; Bildungsromane